Material Requirement Planning Using Algorithme Within Weighting Method in PT XYZ Golf Gloves: Perencanaan Kebutuhan Material Menggunakan Metode Algorithme Within Weighting pada Produk Sarung Tangan Golf PT XYZ - Vici Dariska Mayna; Iriani (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
PT XYZ is a golf glove manufacturing company in Yogyakarta. The company faces serious challenges in the form of delays in the supply of main raw materials, namely sheepskin and goatskin imported from Kenya. This delay results in disruption of production, decreased productivity, and risks to customer satisfaction and the company's reputation. This case study aims to design an effective material requirements planning strategy by implementing the Material Requirements Planning (MRP) method based on the Wagner Within (AWW) Algorithm. The AWW method was chosen because it is able to optimize material planning by minimizing inventory costs by considering fluctuating demand, ordering costs, and storage. The results of the study show that the implementation of AWW-based MRP helps companies calculate material requirements accurately, ensure the supply of raw materials is available on time, and maintain operational efficiency. This system also contributes to minimizing the risk of raw material shortages and excess stock, thus supporting smooth production. AWW-based MRP is an effective solution in improving inventory management, maintaining smooth production, and increasing customer satisfaction. The implications of the study show the importance of a data-driven planning system to overcome supply chain constraints and support the company's competitiveness in the global market.